Differences in symptom reporting between males and females at baseline and after a sports-related concussion: A systematic review and meta-analysis - Brown, D. A.; Elsass, J. A.; Miller, A. J.; Reed, L. E.; Reneker, J. C. (Sports Medicine, 2015)
Concussion literature and treatment guidelines are inconclusive regarding the role of sex in symptom reporting at baseline and post-concussion. Although empirical evidence is lacking, it is generally regarded that females have a more severe symptomatic presentation than males at all time-points on the concussion spectrum. Objectives: Our objective was to determine whether differences exist between males and females at baseline (pre-season/before concussion) or post-concussion for self-reported (1) prevalence of individual symptoms and (2) total symptom scores in high school and college athletes. Design: Systematic review and meta-analysis of observational cohort studies; level of evidence, 1. Methods: A computerized search of the PubMed, SPORTDiscus, CINAHL, and Scopus databases was performed. Meta-analysis Of Observational Studies in Epidemiology (MOOSE) guidelines were followed. Criteria for inclusion were (1) self-report of symptoms at any time within the concussion spectrum, including baseline and after concussion, (2) study sample included high school and/or collegiate athletes aged 12-26 years, (3) concussions occurred during participation in sport, and (4) symptom reporting was separated by sex. The Quality Assessment Tool for Cohort Studies, Q-Coh, was utilized for quality assessment. Results: Twenty-one studies met the criteria for inclusion: seventeen had good quality and four, acceptable quality. At baseline, females had significantly higher odds than males of reporting the individual symptoms of vision/hearing problems, headache/migraine, difficulty concentrating, energy/sleep disturbances, and emotional disturbances. Post-concussion, only one symptom demonstrated significant differences between males and females, with females demonstrating lower odds of reporting confusion than males. Statistically, at baseline and post-concussion, females had significantly higher total symptom scores on the Post-Concussion Scale (PCS) and the Sport Concussion Assessment Tool 2 (SCAT2), but when the standard mean difference was interpreted after back-transformation, these results were clinically insignificant. Conclusions: The symptomatic presentation of males and females, most notably the prevalence of specific symptoms, is very divergent. Females had higher total symptom scores at baseline and post-concussion, however, clinically this cannot be interpreted as a meaningful difference. It is possible that these differences can be explained by normal hormonal changes associated with the menstrual cycle. The implications of these findings are that symptomatic presentation during an individual female`s menstrual cycle needs to be taken into consideration post-concussion when making return-to-play decisions, as returning to a completely asymptomatic level may not be a reasonable expectation.